Gender differences in formal wage employment in urban Tanzania - Kwadwo Opoku; Francisco M. P. Mugizi; Emmanuel Adu Boahen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper uses the latest Tanzania labour force survey-the Integrated Labour Force Survey-and a censored bivariate probit model to analyse gender differences in labour force participation and gender bias in formal wage employment in urban Tanzania. Our findings indicate that, compared to men, women are less likely to participate in the labour market and less likely to get formal wage employment, suggesting the existence of gender bias in the labour market in urban areas of Tanzania. However, after accounting for selection into labour force participation, the existing gender bias is narrowed for women with high school or university education. The regression results suggest that the existing gender differences in formal wage employment probabilities cannot entirely be explained by observable characteristics. The finding of a positive unexplained formal wage employment probability differential suggests that the possibility of gender discrimination against women in urban Tanzania cannot be completely ruled out.
Keywords: J13; J16; J21; J71; 330; labour force participation; formal wage employment; censored bivariate probit model; gender; discrimination; Tanzania